2018
DOI: 10.1002/cpp.2195
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial roots of paranoid ideation: The role of childhood experiences, social comparison, submission, and shame

Abstract: Finding suggests different variables being involved in paranoid ideation, and the specificities of patients with paranoid schizophrenia should be considered in the development of more effective psychotherapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Reportedly, the worse a child is treated, especially by his father, the more frequent is paranoid ideation observed in the adult life (Carvalho et al 2018). Apparently, Putin is sensitive to hints of bullying and fears its re-enactments.…”
Section: Psychological Aspectmentioning
confidence: 99%
“…Reportedly, the worse a child is treated, especially by his father, the more frequent is paranoid ideation observed in the adult life (Carvalho et al 2018). Apparently, Putin is sensitive to hints of bullying and fears its re-enactments.…”
Section: Psychological Aspectmentioning
confidence: 99%
“…Shame is a determining factor of social behavior [33]. In several psychology studies, it was found that Shame arises when someone feels that they are unable to do something, feelings of helplessness, and failure [34].…”
Section: Shamementioning
confidence: 99%
“…In spite of their impact on identity and behavior, or more generally speaking, subjective wellbeing, research on these self-conscious emotions is still very incipient. They often focus on their relationship with depression or anxiety [ 5 ] or on bipolar disorders [ 6 ], on their identification through language or facial expression [ 7 , 8 ], or on isolating and analyzing some of them, such as guilt and shame, because of their connection to anxiety [ 9 ], or with psychotic disorders (shame) [ 10 ], to name a few.…”
Section: Introductionmentioning
confidence: 99%